2021
DOI: 10.1021/acsami.0c18615
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Dynamics in Semiconducting Graphene Quantum Dots Integrated with 2D MoS2 for Optical Enhancement in the Near UV

Abstract: The hybrid structure of zero-dimensional (0D) graphene quantum dots (GQDs) and semiconducting two-dimensional (2D) MoS2 has been investigated, which exhibit outstanding properties for optoelectronic devices surpassing the limitations of MoS2 photodetectors where the GQDs extend the optical absorption into the near-UV regime. The GQDs and MoS2 films are characterized by Raman and photoluminescence (PL) spectroscopies, along with atomic force microscopy. After outlining the fabrication of our 0D–2D heterostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…Min et al reported another hybrid structure comprising zero-dimensional (0D) GQDs and semiconducting 2D MoS 2 that exhibits remarkable properties for optoelectronic devices, outperforming MoS 2 photodetectors [146]. GQDs exhibit unique optoelectronic features such as long carrier lifetimes and rapid electron extraction due to enormous transition energies and weak coupling to excitonic states.…”
Section: Hybrid 2d Quantum Dots Materials and Their Applicationsmentioning
confidence: 99%
“…Min et al reported another hybrid structure comprising zero-dimensional (0D) GQDs and semiconducting 2D MoS 2 that exhibits remarkable properties for optoelectronic devices, outperforming MoS 2 photodetectors [146]. GQDs exhibit unique optoelectronic features such as long carrier lifetimes and rapid electron extraction due to enormous transition energies and weak coupling to excitonic states.…”
Section: Hybrid 2d Quantum Dots Materials and Their Applicationsmentioning
confidence: 99%
“…[72][73][74][75][76][77][78][79] GQDs have the fascinating characteristics of both two-dimensional (2D) graphene and the exceptional physicochemical properties of QDs, namely, quantum confinement effect, non-zero bandgap, and edge effects. 34,[80][81][82][83] Graphene-based quantum dots (GQDs) have been comprehensively explored due to their desirable attributes such as facile, eco-friendly synthesis, low cost, nontoxicity, good biocompatibility, 36,84,85 high stability, controllable chemical functionality, water dispersibility, surface grafting, stable photoluminescence, 73 robust chemical inertness, 26 excellent electrical, and optical properties, abundant functional groups (e.g., hydroxyl, amino, and carboxyl), electron mobility, and huge surface area, endowing them immense potential applications in the optical, 86 energy, 87 electronic, and biomedical fields. 88,[89][90][91][92][93][94][95][96] Owing to their quantum confinement and special edge effects, GQDs show distinct fluorescent properties and physical and chemical properties.…”
Section: Reviewmentioning
confidence: 99%
“…Many fluorescent nanomaterials have been developed and used in biomedicine, especially for bioimaging [ 6 , 7 ]. The discovery of semiconductor quantum dots has opened a new chapter in modern fluorescent nanomaterials [ 8 , 9 ]. Compared with traditional organic dyes, the unique advantages of semiconductor quantum dots, such as high quantum yield, excellent photostability, and fluorescence tenability, make them promising materials in bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%